Polyethylenimine functionalized with dopamine: Characterization and electrocatalytic properties - Rubianes, María Dolores (2010)
We report the chemical modification of polyethylenimine (PEI) by functionalization with dopamine (Do) using glutaraldehyde (Glu) as a linker (PEI-Glu-Do). The new polymer was characterized by FT-IR spectroscopy, by derivative UV-vis spectroscopy, and Cyclic Voltammetry. The PEI-Glu-Do demonstrated to have an important electrocatalytic activity allowing an important decrease in the overvoltages for the oxidation of NADH and a significant increase in its oxidation peaks currents. Different ratios of PEI:Do were assayed and the best response was obtained using PEI:Glu:Do 1:2:1. The new polymer represents an interesting and promising alternative for the electrochemical quantification of NADH and other analytes of clinical interest, as well as for the development of new electrochemical (bio)sensors.